Personality in sport: a comprehensive review - Allen, M. S.; Greenlees, I.; Jones, M. (International Review of Sport and Exercise Psychology, 2013)
This review addresses personality in organised sport. We describe the extant literature that has explored personality effects on athletic success and population-based differences before hypothesising how sport participation may contribute to personality development. We then outline the role of personality in athletic interactions and group processes before considering the practical applications of personality research and avenues for future study. Our review shows that personality is an important determinant of long-term success in sport and identifies clear personality differences between individuals that participate in organised sport and individuals that do not participate in organised sport. We also observe important personality differences between sub-samples of athletes and outline the contribution of personality to intragroup relationships and team effectiveness in team sport. The interaction of genetic and environmental influences is presented as a promising avenue of inquiry that can strengthen our understanding of personality effects on sport and exercise participation and athletic success. We conclude by outlining implications for applied sport psychology.